A study of the hydrodynamics of steam-assisted coal particles removal - Afrasyab, Khan; Khairuddin, Sanaullah; Konstantinovich, Spiridonov Evgeny; Fedorovna, Khabarova Darya; Rigit, Andrew Ragai Henry; Ullah, Atta (Springer Nature, 2021)
The presence of coal particles, as well as the acidic aerosol in the exhaust gases from the coal-fired power plants, present a major threat to the global atmosphere. Here, the hydrodynamics of the orthogonal injection of the steam into the square duct flow channel through which the air containing coal particulates has been investigated. The steam was injected into the flow channel to wet the coal particles to enable their separation from the air based on the particles becoming heavier. The experimental setup used in the present study consisted of the 2 cm × 2 cm square flow duct made of the transparent Perspex and was 50 cm long. The mixture of air and coal particles was introduced at one end of the duct, and a centrifugal rotator was located at the other end of the duct, which was used to separate the coal particles from the wet coal particles from the air. And swirling steam was injected into the duct by two nozzles located at lower and upper surfaces of the duct. PIV images of the flow field at varying steam and air pressure and making use of the measurements of the turbulent fluctuating velocities, relative velocity and transient analysis, spike in removal efficiency of the coal particles from the air was found as 4–7%, corresponding to the range of particle sizes, 0.30–0.45 μm, inlet steam pressure of 1.5 bars and air pressure varying from 0.4 to 3.0 bars. However, the overall separation efficiency was obtained as 51%.